PERBEDAAN KADAR BILIRUBIN TOTAL SERUM LIPEMIK SEBELUM DAN SESUDAH PENAMBAHAN POLYETHYLENE GLYCOL - Alifah Nuraini, Syifa; Riyani, Ani; Kurnaeni, Nani; Wiryanti, Wiwin (Politeknik Kesehatan Kemenkes Bandung, 2024)
Lipemic serum is characterized by its turbid appearance, resulting from elevated concentrations of lipoproteins, particularly chylomicrons and very low-density lipoproteins (VLDL). This turbidity can interfere with the accuracy of total bilirubin measurements, leading to potentially inaccurate results. To mitigate this issue, polyethylene glycol (PEG) is often used as a clarifying agent. This study aims to evaluate the differences in total bilirubin levels in lipemic serum before and afterthe addition of 10% polyethylene glycol 6000. This quasi-experimental research uses a one group pretest-posttest design. conducted in May 2024 at the Clinical Chemistry Laboratory, Department of Medical Laboratory Technology, Bandung Health Polytechnic. A total of 30 serum samples from hospitals in Bandung were combined to make pooled sera, then modified to be lipemic using egg yolk until the triglyceride level reached 991.5; 1002.8; and 1067.8 mg/dL.Total bilirubin levelswere measured both before and after the addition of polyethylene glycol, with initial levels recorded at 1.62, 2.64, and 3.58 mg/dL, and post-PEG levels at 2.40, 3.30, and 4.35 mg/dL. Statistical analysis using a paired sample t-test revealed a significance level of 0.000 (p < 0.05), indicating a significant difference in total bilirubin levels before and after the application of polyethylene glycol in lipemic serum.